The Evolution of the Market of the Hungarian Printing Industry after 1989:The End of a Success Story? - Mihály Laki (Hungarian Academy of Sciences, Institute of Economics, 2010)
This article examines a case study of one industry in order to explore the factors influencing changing performance levels in the industries of post-socialist economies. It explores the influence on industrial performance of a number of once-only non-repetitive factors of market development that were typical of the transition period and compares them with longer term aspects of the market economy. The case that we discuss here is the development of the market for products of the Hungarian printing industry since the late 1980s. During the transition phase, privatisation, deregulation, the abolition of administrative distribution, and radical cuts in subsidies were all among the factors affecting this industry. Its supply chains also changed radically. However, these lost their importance after the transition had been completed and the long term processes of technical development and consumer behaviour became the main determinants of the behaviour of the printing companies.
Keywords: L11; 330; printing industry; post-socialist economies; transition; Druckindustrie; Systemtransformation; Ungarn